Strategi Brand Management pada Brand Lokal: Studi Kasus Erigo dalam Membangun Brand Equity di Pasar Global - Susilaningrum Hartono; Eli Jamilah Mihardja (Economic Reviews Journal, 2025)
This study aims to analyze the brand management strategy implemented by Erigo, a local Indonesian brand, in building and strengthening brand equity in the global market. In facing increasingly tight competition in the era of globalization and digitalization, local brands are required to compete not only in product quality, but also in the ability to build a strong and relevant brand image in the minds of consumers. This study uses a descriptive qualitative approach through literature studies on various scientific sources, including journals, articles, and publications related to brand equity and brand management strategies. The results of the study show that Erigo has succeeded in building global brand equity through five main strategies, namely: repositioning the brand from local streetwear to a travelwear brand with a global identity; implementing aggressive and consistent digital campaigns through social media; strategic collaboration with influencers and Key Opinion Leaders (KOL) to create positive brand associations; participation in the prestigious New York Fashion Week event and placing advertisements in Times Square as a symbol of global existence; and forming a loyal customer community through storytelling and digital activation. Erigo's success is an important case study for other local brands that want to penetrate the international market. These findings emphasize the importance of an integrated, authentic brand management approach based on a deep understanding of global consumer behavior and the power of digital media.